Associations between classroom learning environments, teacher interpersonal behaviour and student outcomes in secondary mathematics classrooms. - Rawnsley, David G. (Curtin University, 1997)
The classroom learning environment has increasingly been recognised as an important factor in education. However, over recent years the increasing research in this area has focussed on humanities or science classrooms. Virtually no investigations have been reported into the learning environment of the secondary mathematics classroom.The study reported in this thesis focusses on the perceptions of 490 grade 9 mathematics students in 23 classrooms in 14 schools in Adelaide, South Australia. Students' perceptions of their mathematics learning environment were measured using a new classroom environment instrument which has been developed in both a Personal Form (which focusses on students' perceptions of their personal interaction with the learning environment) and a Class Form (which focusses on students' perceptions of the class's interactions with the learning environment).This study confirmed the reliability and validity of both forms of the new instrument in its use with this sample of students, and examined the differences between the Personal and the Class Forms of the instrument. The sub-populations of male and female students were also profiled and differences between their perceptions of the classroom learning environment were examined. Differences between students' perceptions of their teacher's interpersonal behaviour in the classroom were also explored.The study identified associations between students' perceptions of their mathematics classroom learning environment, their perceptions of their teacher's interpersonal behaviour, and student outcomes. The association between students' perceptions of their mathematics classroom environment and attitudinal outcomes was stronger than the association with cognitive outcomes.Finally, the commonality and uniqueness of the two instruments measuring classroom learning environment and teacher's interpersonal behaviour in terms of predicting outcome variance were established, as were associations between the perceptions of students in these two areas.